The effect of efficiency measurement to the improvement of maintenance productivity - Rizlan, Wardah; Hadi Purba, Humiras; ., Hasbullah; ., Saryanto; Nasir, Mohamad; Aisyah, Siti (International Journal of Engineering and Technology, 2019)
Industrial revolution from manual process to automation, digital, integrated between system make changing of demand on the performance of machinery or equipment. Efficiency and productivity are no longer calculated based on the output generated by the operators working in a process. Efficiency and productivity are calculated from the output of a machine or process that is integrated automatically. The need for regular maintenance of machinery or equipment is one of the main needs of manufacturing. In addition, the need for maintenance work is also a major concern. Performance of maintenance is not only measured from OEE (Overall Equipment Effectiveness) but also measured by the efficiency of their activity. Identification of Non Added Value (NVA) activity related to maintenance activity should be done to see improvement opportunities. In the end of investigation, we can increase efficiency from 20.4% to 49,5% by reduce NVA activity. From data of efficiency, we can calculate the number of maintenance personnel required, from 6 people to 4 people. This research to avoid shortage or excess man power resulting and impacted to decreased of efficiency and productivity for both the machine and the maintenance itself.Â Â